2009
DOI: 10.1128/aem.02567-08
|View full text |Cite
|
Sign up to set email alerts
|

Coral-Associated Bacteria and Their Role in the Biogeochemical Cycling of Sulfur

Abstract: Marine bacteria play a central role in the degradation of dimethylsulfoniopropionate (DMSP) to dimethyl sulfide (DMS) and acrylic acid, DMS being critical to cloud formation and thereby cooling effects on the climate. High concentrations of DMSP and DMS have been reported in scleractinian coral tissues although, to date, there have been no investigations into the influence of these organic sulfur compounds on coralassociated bacteria. Two coral species, Montipora aequituberculata and Acropora millepora, were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
335
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 396 publications
(343 citation statements)
references
References 72 publications
(107 reference statements)
4
335
0
4
Order By: Relevance
“…Recent studies, however, indicate that other members of the coral holobiont (in particular Symbiodinium dinoflagellates) also influence microbial community structure through release of complex carbon-containing exudates including dimethylsulfoniopropionate (DMSP; Ikeda and Miyachi, 1995;Raina et al, 2009Raina et al, , 2010. DMSP can be degraded to dimethylysulphide, a central molecule in the global sulphur cycle, which diffuses from the ocean into the atmosphere where it influences cloud formation, with consequences for atmospheric chemistry, local climate and water temperature (Ayers and Gras, 1991;Andreae and Crutzen, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, however, indicate that other members of the coral holobiont (in particular Symbiodinium dinoflagellates) also influence microbial community structure through release of complex carbon-containing exudates including dimethylsulfoniopropionate (DMSP; Ikeda and Miyachi, 1995;Raina et al, 2009Raina et al, , 2010. DMSP can be degraded to dimethylysulphide, a central molecule in the global sulphur cycle, which diffuses from the ocean into the atmosphere where it influences cloud formation, with consequences for atmospheric chemistry, local climate and water temperature (Ayers and Gras, 1991;Andreae and Crutzen, 1997).…”
mentioning
confidence: 99%
“…These OTUs are all affiliated with species implicated in the metabolism of complex organic molecules such as DMSP and dimethylysulphide. For example, previous studies have identified abundant bacteria within the Oceanospirillales that are able to metabolise DMSP in the coral Acropora millepora (Raina et al, 2009 Figure 1 Redundancy analysis (RDA) summarising variation in the composition of marine invertebrate-associated microbial communities that was attributable to the presence-absence of photosymbionts. The filled shapes represent individual samples collected from each invertebrate species.…”
mentioning
confidence: 99%
“…Two different basal media were used to determine the DMSP metabolic capabilities of V. coralliilyticus: a modified marine ammonium salt medium (Raina et al, 2009) lacking any carbon source, and a modified basal salt medium lacking any sulfur source (Fuse et al, 2000). DMSP was added to both the media (1 mM final concentration) and acted either as a sole carbon source or as a sole sulfur source.…”
Section: Mucus Collection On Davies Reef (Great Barrier Reef)mentioning
confidence: 99%
“…DddD homologs occur not only in marine a-and gproteobacteria that were already known to have Ddd ĂŸ phenotypes, but also in the terrestrial bacteria, Burkholderia ambifaria and Rhizobium NGR234, both of which, perhaps significantly, interact with higher plants . Raina et al (2009) recently isolated g-and a-proteobacteria that grew on DMSP as sole carbon source from the mucus or skeletons of the coral Montipora, which interacts with DMSP-containing zooxanthellae (Hill et al, 1995). Having shown here that at least some fungi that associate with corals have a Ddd ĂŸ phenotype, it will be of interest to know the relative contributions of bacteria and Column (1) shows A. sydowii strains as in Rypien et al (2008).…”
mentioning
confidence: 99%